Механізм управління мотивацією персоналу логістичного підприємства - Ковальський, В. С.; Kovalskyi, V. S.; Пушкар, О. І.; Pushkar, O. I.; Кравченко, Н. В.; Kravchenko, N. V. (Економіка та суспільство. - 2020. - Вип. 22., 2020)
Досліджено мотиваційне середовище, що позитивно впливає на ефективну роботу співробітників підприємства, а також проаналізовано механізм управління мотивацією персоналу на підприємстві логістичної сфери. Розглянуто теорії мотивації та розкрито поняття мотиваційного середовища. Визначено сутність та специфічні особливості механізму формування мотиваційного середовища на підприємстві логістичного напряму. Окреслено роль корпоративної культури у ланцюгу формування позитивної мотивації співробітників. Деталізовано завдання, функції та принципи побудови мотиваційного механізму персоналу компанії логістичної сфери. Обґрунтовано, що механізм управління мотивацією і корпоративний розвиток персоналу забезпечують розвиток кожного працівника логістичного підприємства окремо і створюють умови для формування мотивів участі в капіталізації підприємства.

The article is devoted to the study of the motivational environment of the enterprise, which can positively affect the efficiency of the employees of the enterprise. It was revealed that in the scientific literature there is a limited number of definitions of the term "motivational environment" and is practically absent – "motivational and logistic environment" and there is no clear mechanism for managing staff motivation at an enterprise in the logistics sector. In the course of the study, the theory of motivation is analyzed and the concept of a motivational environment at a logistics enterprise is revealed. It is understood as a set of activities and conditions defined within the corporate culture of a logistics company, motivating personnel to ensure effective performance both in managing logistics flows in supply chains, and their continuous improvement based on knowledge capitalization. The essence and specific features of the motivational environment at the enterprise of the logistics direction have been determined and the tasks and functions of building a motivational mechanism have been developed. The role of corporate culture in the chain of forming positive motivation of employees has been determined. The article details the principles of building a motivational mechanism for personnel in a logistics company and outlines the main trends in personnel motivation management: the support of spirits to the quick acceptance of logistic decisions by the way of activating them logical-ly and intuitively; formulating the interest of sportsmen before evaluating the power decisions for the participants and setting up their own meeting in the public; the formulation of motives for the conversion of power with the accounting of the hundred pardons; development of professional health, mastery in the minds of self-reliance, the logistic vibra-tion is straightforward, intuitively, and to create an optimal system and management of financial flows. It has been substantiated that the mechanism of motivation management and corporate development of personnel ensure the development of each employee of a logistics enterprise separately and create conditions for the formation of motives for participation in the capitalization of the enterprise.

Исследована мотивационная среда, что положительно влияет на эффективную работу сотрудников предприятия, а также проанализирован механизм управления мотивацией персонала на предприятии логистической сферы. Рассмотрены теории мотивации и раскрыто понятие мотивационной среды. Определена сущность и специфические особенности механизма формирования мотивационной среды на предприятии логистического направления. Охарактеризована роль корпоративной культуры в цепи формирования положительной мотивации сотрудников. Детализированы задачи, функции и принципы построения мотивационного механизма персонала компании логистической сферы. Обосновано, что механизм управления мотивацией и корпоративное развитие персонала обеспечивают развитие каждого работника логистического предприятия отдельно и создают условия для формирования мотивов участия в капитализации предприятия
The mechanism for managing staff motivation in a logistics enterprise
Keywords: логістичне підприємство; logistics enterprise; логистическое предприятие; мотивація персоналу; personnel motivation; мотивация персонала; корпоративна культура; corporate culture; корпоративная культура; мотиваційне середовище; motivational environment; мотивационная среда; інтелектуальна капіталізація; intellectual capitalization; интеллектуальная капитализация